2006
DOI: 10.1016/s1472-6483(10)60654-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of duration and dose of gonadotrophins on IVF outcomes

Abstract: In order to examine whether the duration of the follicular phase and changes in daily gonadotrophin dosages impact IVF outcome, a retrospective analysis of women who underwent oocyte retrieval and fresh embryo transfer was performed. Among the parameters assessed were the number of days of gonadotrophin stimulation, changes in the daily dosage of gonadotrophins, total ampoules of gonadotrophins, embryo implantation rates, clinical pregnancy rates and ongoing pregnancy rates. The number of days of gonadotrophin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
2
34
1
1
Order By: Relevance
“…Martin et al recently reported no effect of the length of gonadotropin stimulation on clinical pregnancy following ART in a univariate analysis of 555 cycles [12]. Several potential differences between our studies may account for [10,14]; thus, lack of correspondence of body composition between the two studies may explain the lack of agreement.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Martin et al recently reported no effect of the length of gonadotropin stimulation on clinical pregnancy following ART in a univariate analysis of 555 cycles [12]. Several potential differences between our studies may account for [10,14]; thus, lack of correspondence of body composition between the two studies may explain the lack of agreement.…”
Section: Discussioncontrasting
confidence: 51%
“…Using a univariate analysis, a recent study reported that the length of stimulation did not affect clinical pregnancy outcomes following ART [12]. A number of parameters may influence both the duration of gonadotropin stimulation and the likelihood of success, and, thus, constitute potential confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Martin ve ark. 555 adet siklusla yaptıkları çalışmada gonadotropin stimülasyon süresinin ve dozunun gebelik sonuçlarını etkilemediğini rapor etmişlerdir (25) . Bizim çalışmamızda, toplam kullanılan gonodotropin dozunun ve stimülasyon süresinin gebelik başarısını etkilemediği ancak yaş grupları arasında Grup 1'de Grup 3'e göre stimülasyon süresinin istatistiksel olarak anlamlı uzun olduğu gözlenmiştir.…”
Section: Discussionunclassified
“…When the clinicians identify a patient's responsiveness class before the COH cycle, typical predictive factors involve her medical characteristics such as age, BMI, previous IVF-ET experience(s), number of antral follicles (follicles with diameter 2-5 mm), and ovary diameters, the last two of which are related to the diagnosis of PCOS (Martin et al 2006;Chang et al 1998;Ku et al 2006). In this study, all patients are with PCOS or PCOS potential, Fig.…”
Section: The Objective Functionmentioning
confidence: 90%